Aspek Teknis Budidaya Dan Profitabilitas Pendederan Ikan Nila Merah (Oreochromis niloticus) Studi Kasus Di Turbo Farm, Kota Bogor Jawa Barat - Yani Hadiroseyani; Apriana Vinasyiam; Chandrika Agustiyana (Jurnal Akuakultur Sungai dan Danau, 2022)
Nursery culture of tilapia (Oreochromis niloticus) is an important segment to support a comprehensive tilapia culture business. Requirements for business sustainability involve the high profitability of the company and high growth of the reared fish. This experiment aimed to observe the profitability aspect, fish growth, water quality, and culture techniques applied in a tilapia farm. The experiment was done using case study method, where Turbo farm, located  in Bogor West Java, was used as a model. The data collected involved primary data from field observation and secondary data from interview activities. The results showed that tilapia juvenile had a good growth, and that the water quality (temperature and pH) ranged within optimal range for tilapia culture. At stocing density of 2.000 juvenile per production unit in one cycle, the total production was 68.400 juvenile per year, in which 10% of the total produced juvenile were sold at size of 7-8 cm, while the remaining juveniles were at size 11-12 cm. Price of juvenile at size 7-8 cm was half of the size 11-12 cm, Rp 600 vs Rp 1.200 per juvenile, respectively. The profit of the business was Rp 43.989.000 per year with value of revenue/cost (R/C) ratio 2,29, and payback period (PP) 6,27 year. Based on the previously mentioned profitability parameters, the nursery culture of tilapia performed by Turbo farm was profitable. However, an efficiency of facility use was needed to increase profit and shorten the return on investment period.